Socio-Economic Resilience of Ukraine as an Imperative of the Policy of Strengthening Migration Security and Minimizing Vulnerability - MULSKA, Olha; VASYLTSIV, Taras; IVANIUK, Ulana; ROMANCHUKEVYCH, Maryana; KUTSYK, Valentyna; IABLON, Volodymyr (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025, 2025)
The management of migration processes in terms of ensuring their volumes within optimal limits to minimize social vulnerability is an imperative of the policy of ensuring socio-economic resilience in the context of instability, crisis, and the deepening of new challenges. The article aims to analyze the social vulnerability of Ukraine (on the example of the oblasts of the Carpathian region) in the context of the migration crisis and the weakening of security factors in 2010-2023 as determinants of reduced resilience of socio-economic systems. Based on the calculated composite indicators of social vulnerability, the authors find that the human resource donor regions (the oblasts of the Carpathian region of Ukraine) demonstrated a critical situation of social vulnerability of the population with a tendency to approach the lower marginal threshold, which significantly weakened their migration security and led to a decrease in the socio-economic resilience of the country. The study reveals that the region demonstrated a critical situation of social vulnerability of the population with a tendency to approach the lower marginal threshold (the indicator in the Carpathian region of Ukraine was 0.499). The main triggers for the spread of social vulnerability, and thus the weakening of social resilience, included a decline in the standard of living, disruption of the demographic balance, and the poor quality of the social and labor sphere. In 2010-2015, the trend of ensuring social resilience in the Carpathian region reproduced to the national one, with the highest value of the divergence indicator in 2010 (3.2 pp) and the lowest in 2020 (0.9 pp). The results of the empirical study show that declining living standards, demographic imbalances caused by high migration activity, and structural imbalances in regional labor markets were the main triggers for the spread of social vulnerability and, consequently, the weakening of resilience. The conceptual model of the mechanism envisages analysis of the environment (identification of geopolitical and socio-economic factors influencing migration and assessment of current and potential threats), definition of goals and objectives, drafting scenarios for the development of the migration situation and the impact of each scenario on national security, selection of optimal solutions, and development of alternative planning for socio-economic resilience.